Musicology: The Key Concepts - Leon Stefanija (Muzikološki Zbornik, 2017)
David Beard and Kenneth Gloag. Musicology: The Key Concepts (second edition). (London and New York: Routledge, 2016. 360 pp. Hardback £80. Paperback and E-book £22.99. ISBN-13: 978-0415679671.)